HEALTH INSURANCE IN HEALTH REFORM IN UKRAINE - H. Tlusta (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The author of the article researched the teoretical and methodological approaches to the formation and development of the health insurance market conditions, also investigated the condition and features of the functioning of the health system in Ukraine and abroad, reasonable prospects of introducing mandatory and dissemination of voluntary health insurance, as well as ways of improving financial provide health insurance system in Ukraine.